Jailbreak recurrence as a new security threat in Nigeria (2019)
Nigeria Prisons Service is one of thè three arms of thè nation's criminal justice System; thè other two are thè police and thè courts. Prisons or jails are designed to accommodate any individuai or group of people, male or female, found to have broken thè law. However, inmates of such facilities sometimes forcefully free themselves from this confinement. This is referred to as jailbreak. Jailbreak has become a new form of threat to Nigeria's internai security. This paper examined thè emerging threat of jailbreak in Nigeria, thè implications of this trend on thè part of thè prisoners, prison officials, other law enforcement agencies and thè communities where prisons are located. Synthesised primary and secondary sources of data were used including key informant interviews and literature. This paper concludes that embarking on prisons reforms as an option for checkmating jailbreaks and would make prisons officials more accountable than what is presently obtainable.